Discovery of deoxyceramides and diacylglycerols as CD1b scaffold lipids among diverse groove-blocking lipids of the human CD1 system. - Huang, S; Cheng, T; Young, D; Layre, E; Madigan, C; Shires, J; Cerundolo, V; Altman, J; Moody, D (2011)
Unlike the dominant role of one class II invariant chain peptide (CLIP) in blocking MHC class II, comparative lipidomics analysis shows that human cluster of differentiation (CD) proteins CD1a, CD1b, CD1c, and CD1d bind lipids corresponding to hundreds of diverse accurate mass retention time values. Although most ions were observed in association with several CD1 proteins, ligands binding selectively to one CD1 isoform allowed the study of how differing antigen-binding grooves influence lipid capture. Although the CD1b groove is distinguished by its unusually large volume (2,200 Å(3)) and the T' tunnel, the average mass of compounds eluted from CD1b was similar to that of lipids from CD1 proteins with smaller grooves. Elution of small ligands from the large CD1b groove might be explained if two small lipids bind simultaneously in the groove. Crystal structures indicate that all CD1 proteins can capture one antigen with its hydrophilic head group exposed for T-cell recognition, but CD1b structures show scaffold lipids seated below the antigen. We found that ligands selectively associated with CD1b lacked the hydrophilic head group that is generally needed for antigen recognition but interferes with scaffold function. Furthermore, we identified the scaffolds as deoxyceramides and diacylglycerols and directly demonstrate a function in augmenting presentation of a small glycolipid antigen to T cells. Thus, unlike MHC class II, CD1 proteins capture highly diverse ligands in the secretory pathway. CD1b has a mechanism for presenting either two small or one large lipid, allowing presentation of antigens with an unusually broad range of chain lengths.